(untitled) (Strathmore Law Journal, 2017)
Numerous reports in the last decade have focused on the challenges to African economies that emanate from the illicit transfers of funds and other valuable assets within some global corporations. A primary concern is the impact of these transfers on the taxable income of African subsidiaries. Two broad categories of intra-group transfers are of particular interest, partly because of the complexities they raise. One comprises transfers in payment of services exchanged among associated enterprises, while the other pertains to transfers by subsidiaries in payment of the value of intellectual assets attributed to the corporate centre of the global corporation. This article highlights the challenges raised by these transfers through case studies. It examines possible mechanisms to mitigate the challenges, drawing attention to current and impending developments. It concludes that there are good prospects for curbing illicit transfers linked to the examined types of transactions.